Comparison between Effects of Fentanyl and Fenofol as Sedative in Elective Caesarean Section under Subarachnoid Anaesthesia - Md Enayet Karim; Mohammad Saleh Akram; RAM Mustafijur Rashid; Reza Ershad; Md Muzibur Rahman (KYAMC Journal, 2023)
Background: Regional anaesthesia has become an important anaesthetic technique now a days. Pharmacologically induced tranquility improves acceptance of regional technique. Objective: To compare Fentanyl and Fenofol (Fentanyl+Propofol) in terms of onset and recovery of sedation, haemodynamic effects, respiratory effects and adverse effects of both the drugs during elective Caesarian section under spinal(subarachnoid) anaesthesia. Materials and Methods: This randomized clinical trial included 60 ASA (American Society of Anaesthesiologists) grade I or II patients between age 20-40 years undergoing elective Caesarean sections under Subarachnoid anaesthesia during the period January 2022 to June 2022. Patients were randomly allocated to one of two groups: Fentanyl group (Group F, n=30), who received Fentanyl in a single dose of 0.5mcg/kg and Fenofol group (Group FP, n=30), who received Fenofol in a single dose of Fentanyl-0.5mcg/kg+Propofol-0.5mg/kg. Spinal anaesthesia was conducted by injecting a hyperbaric solution of 0.5% bupivacaine 3ml through a 25G spinal needle at L3-4 level. All parameters were documented at 5 min intervals until arousal of the patient. The onset of sedation i.e. time from iv (intravenous) injection of Fentanyl or Fenofol to closure of eye lids (OAA/S score of 3) and the arousal time from sedation i.e. time from closing of the eye lids to OAA/S score of 5 ( patient is awake clinically) were noted. Any complication during operation was documented. The patient’s satisfaction with the sedation was assessed by the 5 point ‘Likert verbal rating scale.’ Results: There was no significant difference of mean blood pressure and mean heart rate between the two groups in different time intervals (P>0.05). Time of onset of sedation and the arousal time i.e. duration of sedation was comparable between the two groups (P>0.05). Significant percentage of patients required O2 supplementation in Fenofol group due to hypoventilation (66.66% vs 10%, P<0.001). Pain in arm during drug administration was significantly more with Fenofol (46.66% vs 6.66%, P<0.001). Conclusion: As a significantly higher percentage of patients required O2 supplementation during sedation with Fenofol and pain in arm during drug administration was significantly more in Fenofol group, it is recommended that Fentanyl is a better choice than Fenofol for sedation in single dose technique during subarachnoid block for Caesarean section. KYAMC Journal Vol. 13, No. 04, January 2023: 234-239